Comparison of rotational atherectomy and modified balloons prior to drug-eluting stent implantation for the treatment of heavily calcified coronary lesions. Issue 12 (26th March 2021) - Hong, Xu-Lin; Li, Ya; Zhou, Bin-Quan; Fu, Guo-Sheng; Zhang, Wen-Bin
Abstract : Abstract: The optimal strategy for lesion preparation in heavily calcified coronary lesions (HCCL) prior to drug-eluting stent (DES) implantation remains debatable. This study sought to compare the performance of rotational atherectomy (RA) and modified balloon (MB)-based strategy in patients with HCCL receiving current-generation DES. This retrospective study comprised 564 consecutive patients who underwent RA (n = 229) or MB (n = 335) for HCCL at our hospital and were treated with DES. Baseline clinical and angiographic data was obtained from our database. Patients were clinically monitored for the occurrence of any adverse events during the hospitalization. One-year follow-up was conducted by either telephone contact or outpatient visits. 1:1 propensity score matching (PSM) was performed to balance the baseline covariates. After PSM, the clinical outcomes between the 2 groups were compared. After PSM, except more target lesion in right coronary artery existing in the RA group ( P = .008), no significant statistical differences were shown in regard of the other angiographic and procedural characteristics of the 2 groups. Strategy success rates were all 100% in both groups. In the unadjusted Cox proportional hazard analysis, participants with RA had a significantly lower risk of target lesion revascularization (TLR) (hazard ratio, HR 0.275, 95% confidence intervals, CI 0.119–0.635, P = .003) and major adverse cardiac event (MACE) (HR 0.488, 95% 0.277–0.859, P = .013). After adjusting for potential confounding variables, RA was significantly associated with TLR (HR 0.32, 95% 0.12–0.853, P = .023), but no longer significantly associated with MACE (HR 0.674, 95% 0.329–1.381, P = .282). In patients with HCCL, lesion preparation with RA was safe and could improve strategy success rate. There was lower rate of TLR with RA, however, no significant difference was found in the MACE rate at 1-year follow-up between RA and MB-based strategy.